2005
DOI: 10.1002/pen.20336
|View full text |Cite
|
Sign up to set email alerts
|

Melt compounding of different grades polystyrene with organoclay. Part 3: Mechanical properties

Abstract: We discuss the effects of the melt compounding variables, matrix molecular weight and organoclay content on the X‐ray diffraction (XRD) and mechanical properties of polystyrene (PS)/organoclay nanocomposites (PNC) prepared in a twin‐screw extruder. An increase of residence time reduced the height of the first XRD peak and increased that of the second peak. Barrel temperature and screw configuration had a little influence on the tensile properties and impact strength. Young's modulus increased with organoclay c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 32 publications
7
35
0
Order By: Relevance
“…Mechanical properties of the nanocomposites were indicated in figure 2. Figure 2 (a) and (b) showed that nanoclay up to 1 w% contributed to an improvement of the mechanical properties as mentioned before by researchers [12,13]. Increase of the properties was due to the orientation of the nanoparticles in tension direction led to higher strength and also delayed in fracture due to the damping of the stress done by nanofiller layers.…”
Section: Resultssupporting
confidence: 58%
“…Mechanical properties of the nanocomposites were indicated in figure 2. Figure 2 (a) and (b) showed that nanoclay up to 1 w% contributed to an improvement of the mechanical properties as mentioned before by researchers [12,13]. Increase of the properties was due to the orientation of the nanoparticles in tension direction led to higher strength and also delayed in fracture due to the damping of the stress done by nanofiller layers.…”
Section: Resultssupporting
confidence: 58%
“…On the basis of our results and on the data reported in literature [6,28,33], it clearly appears that the delamination of a nanocomposite hybrid reprocessed with a single screw extruder cannot be improved but even reduced by silicate re-agglomeration.…”
Section: Resultsmentioning
confidence: 70%
“…Multiple crazes, which are initiated and terminated by the added rubber particles, are commonly accepted as the toughening mechanism of HIPS [11][12][13]. However, inorganic particles such as silica, montmorillonite and CNTs, which have been shown to have positive effects on the tensile properties, including modulus and elongation-at-break, have insignificant influence on the impact toughness of PS [14][15][16]. Good dispersion of fillers, especially nano-sized particles in a polymer matrix, is an important prerequisite to high impact toughness.…”
Section: Introductionmentioning
confidence: 98%
“…In situ polymerization of styrene in the presence of surface-modified fillers is a common method of preparing various PS composites. For example, surface-treated CNTs or silica particles encapsulated by styrene droplets were used to produce composites with well dispersed fillers upon polymerization [14,17]. In this work, we prepared PS/HNT nanocomposites by emulsion polymerization of styrene in a suspension of HNTs with sodium dodecyl sulfate (SDS) as a dispersing agent for the HNTs.…”
Section: Introductionmentioning
confidence: 99%